Fetal Thymus Size in Pregnant Women with COVID-19 Infection - Goncu Ayhan, Sule; Oluklu, Deniz; Sinaci, Selcan; Atalay, Aysegul; Erol, Seyit Ahmet; Ozden Tokalioglu, Eda; Yildirim, Muradiye; Moraloglu Tekin, Ozlem; Sahin, Dilek (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: To determine the effect of SARS-CoV-2 infection on fetal thymus size by ultrasound. STUDY DESIGN: In this prospective study sonographic fetal thymus size was measured in pregnant women attending our hospital with confirmed SARS-CoV-2 infection by RT-PCR test and age-matched control group. The anteroposterior thymic and the intrathoracic mediastinal diameter was determined in the three-vessel view and their quotient, the thymic-thoracic ratio, was calculated. Results were compared between these two groups. RESULTS: Thirty-six SARS-CoV-2-infected and 47 control group pregnant women were included in this study. Two groups were similar in terms of demographic features and no difference was found for fetal thymus size. CONCLUSION: COVID-19 seems to have no adverse effect on fetal thymus size in mild and moderate patients during the acute phase of the infection.